NEW TRENDS IN MARKETING MANAGEMENT: CONCEPTUAL FRAMEWORK - Arshi Naim (American Journals, 2022)
Marketing Management identifies market opportunities and comes out with appropriate strategies for exploring those opportunities profitably. It has to implement marketing program and evaluate continuously the effectiveness of marketing-mix. It has to remove the deficiencies observed in the actual execution of marketing plans, policies, and procedures. It looks after the marketing system of the enterprise. Management is the process of getting things done in an organized and efficient manner. Marketing management aims at efficient operation of marketing activities. Marketing management smoothen the process of exchange of ownership of goods and services from seller to the buyer. Marketing management, like all other areas of management comprises of the function of planning, organizing, directing coordinating and controlling. This research article presents the conceptual framework of marketing management.
Keywords: Marketing Management, Marketing Mix, planning, organizing, Directing, Coordinating, Controlling.